CYTOTOXIC ACTIVITY AND PHYSICOCHEMICAL PROPERTIES OF GENDARUSIN A-E COMPOUNDS ON ESTROGEN ALFA RECEPTORS (2JF9) - Indrawijaya, Yen Yen Ari; Octavia, Nur Ika; Mutiah, Roihatul; Bhagawan, Weka Sidha; Ma'arif, Burhan (Journal of Islamic Pharmacy, 2019)
Estrogen Alfa (ERÎ±) is a receptor used as the main marker to identify the presence of tumors in the breast.compounds Gendarusin A-E have anticancer activity by inhibiting the poliferation of cancer cells and inducing apoptosis. The purpose of this research are to predict the cytotoxic activity, physicochemical properties, and toxicity of the gendarusin A-E compound. The predictions of physicochemical properties were tested in compliance with the Five Lipinski Rules and the results of the ADME process (absorption, distribution, metabolism, and excretion) using the application pkCSM Online tool. Prediction of cytotoxic activity using Molegro Virtual Docker (MVD) by validating receptors and molecular docking. Cancer receptor protein used in Estrogen Alfa with PDB code 2JF9. Toxicity prediction using the Protox II Online tool. The results of this study indicate that the Gendarusin A-E compound didnâ€™t completed the Five Lipinski Rules. Gendarusin A-E compounds had activity against receptors Estrogen Alpha which is shown by the results of RMSD 2 and Gendarusin A compounds had the smallest Rerank Score of -70.9817 compared to other compounds. Gendarusin B compound had the highest LD50Â  1212 mg / kg and classified in grade 4.